Hypercalcemia of malignancy caused by parathyroid hormone-related peptide-secreting pancreatic neuroendocrine tumors (PTHrP-PNETs): Case Report - Pitts, Stephanie; Mahipal, Amit; Bajor, David; Mohamed, Amr (Frontiers in Oncology, 2023)
Parathyroid hormone-related protein (PTHrP) secretion is occasionally detected in various solid tumors such as renal cell carcinoma and lung cancers. It is considered quite rare for neuroendocrine tumors with only few published case reports. We reviewed the current literature and summarized a case report of a patient with metastatic pancreatic neuroendocrine tumor (PNET) presenting with hypercalcemia due to elevation of PTHrP. The patient had histological confirmation of well-differentiated PNET and developed hypercalcemia years after his initial diagnosis. In our case report, evaluation showed intact parathyroid hormone (PTH) in the setting of concomitant elevation of PTHrP. The patient’s hypercalcemia and PTHrP levels were improved by using a long-acting somatostatin analogue. In addition, we reviewed the current literature regarding the optimal management of malignant hypercalcemia due to PTHrP-producing PNETs.